The analysis of price formula differences - J. J. Doppegieter; I. J. Lambrechts (South African Journal of Business Management, 1985)
In this article, the third in a series of four, accent has been placed on a dynamic analysis of differences between the two price formulae introduced and discussed in the first article. Four different formulae components were analysed by comparing the resulting incremental changes of the internal rates of return for the two price formulae. It appeared that the substantial differences between the internal rates of return of the two formulae, identified in the previous article, are mainly a function of two formulae components, i.e. the valuation method of fixed assets and the profitability rate allowed. The method of analysis, presented in this article, could be a meaningful means of analysing alternative formula components and selecting and defining a viable financial policy.
Keywords: 650